2018
DOI: 10.1021/acsmedchemlett.8b00013
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Orally Bioavailable Selective Inhibitors of the Sodium-Phosphate Cotransporter NaPi2a (SLC34A1)

Abstract: Sodium-phosphate cotransporter 2a, or NaPi2a (SLC34A1), is a solute-carrier (SLC) transporter located in the kidney proximal tubule that reabsorbs glomerular-filtered phosphate. Inhibition of NaPi2a may enhance urinary phosphate excretion and correct maladaptive mineral and hormonal derangements associated with increased cardiovascular risk in chronic kidney disease-mineral and bone disorder (CKD-MBD). To date, only nonselective NaPi inhibitors have been described. Herein, we detail the discovery of the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…It is conceivable that PF-06869206 needs to be administered more frequently to maintain adequate plasma levels or that factors other than phosphate contribute to FGF23 production in CKD. Our studies confirmed those by Thomas et al (49), namely that an acute reduction in PTH levels occurs in wild-type mice upon treatment with a single dose of PF-06869206. However, there was no PTH-lowerring effect of the NPT2a inhibitor upon repeat dosing in 5/6 nephrectomized rats.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…It is conceivable that PF-06869206 needs to be administered more frequently to maintain adequate plasma levels or that factors other than phosphate contribute to FGF23 production in CKD. Our studies confirmed those by Thomas et al (49), namely that an acute reduction in PTH levels occurs in wild-type mice upon treatment with a single dose of PF-06869206. However, there was no PTH-lowerring effect of the NPT2a inhibitor upon repeat dosing in 5/6 nephrectomized rats.…”
Section: Discussionsupporting
confidence: 92%
“…Acute administration of PF-06869206 at 300mg/kg to Npt2c -/mice ( Figures 3A-D In contrast to the findings in wild-type and Npt2c -/mice, administration of PF-06869206 in Npt2a -/mice failed to increase urinary phosphate excretion or to decrease plasma phosphate relative to vehicle or baseline levels at 2-4 hours or 24 hours after dosing (Figures 3E,F). These findings confirmed our in vitro data (49), namely that PF-06869206 selectively inhibits Npt2a and has no readily detectable phosphaturic activity in the absence of that transporter.…”
Section: Acute Administration Of Pf-06869206 Increases Phosphate Excrsupporting
confidence: 90%
See 2 more Smart Citations
“…The compound 376 was screened for their Sodium-Phosphate Cotransporter NaPi2a (SLC34A1) inhibitor activity and compound 376 (NaPi2a IC 50 ¼ 380 nM) was found to be good NaPi2a inhibitor. Compound 376 (PF-06869206) was the first orally bioavailable selective NaPi2a inhibitor and represented a pharmacological tool to probe the functional effects of selective NaPi2a inhibition in vivo [129].…”
Section: Chlorine Containing Drugs As Miscellaneous Applicationsmentioning
confidence: 99%